PENGARUH PEMBERIAN TELUR AYAM DAN TELUR BEBEK TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM - Novita Sari; Ardhita Listya Fitriani; Hermeksi Rahayu; Fitria Hikmatul Ulya; Sus Prantiasih (Midwifery Care Journal, 2022)
Postpartum is a period of recovery of reproductive organs that undergo changes during pregnancy and childbirth, such as the occurrence of perineal tears. This type of research is quantitative and uses a quasi-experimental research design (quasi-experimental). Two Group Pre-Post Test Design, namely two groups given different interventions, namely group one receiving chicken egg therapy intervention and group two receiving duck egg therapy. The study population was all postpartum mothers who had perineal injuries. The total sample size obtained was 18 samples. The sampling technique used is a purposive sampling technique. Based on the results of 18 respondents who were given duck eggs it was known to have an average of 6.28 with a median of 6, while those given chicken eggs had an average value of 6.67 with a median of 7. The results of the analysis of the Mann Whitney U test can be seen that the p value is 0.021 (0.05), so it can be said that there is an effect of the effectiveness of giving chicken eggs and duck eggs on perineal wound healing in postpartum mothers in the Batang II Health Center Work Area, Batang Regency. It is possible that the effect of therapy giving duck eggs and chicken eggs is seen from the composition of duck eggs which is greater than 50% of chicken eggs. The yolk is also larger with a thicker and softer texture than ordinary chicken eggs